Stakeholder Collaboration in Efforts to Enhance International Tourist Visits to Batu Lumbang Mangrove Ecotourism, Pemogan Village, Bali - I Putu Arya Bagus Prakarsa Adiputra; I Ketut Antara; I Gusti Ngurah Widyatmaja (International Journal of Economics, Business and Innovation Research, 2024)
Tourism development in Bali has seen rapid growth, attracting millions of visitors annually. However, excessive exploitation of natural resources and environmentally unfriendly infrastructure threaten ecosystem balance. In response, ecotourism has emerged as a strategy for sustainable tourism development. Mangrove Ecotourism in Batu Lumbang, Desa Pemogan, shows significant potential but faces challenges such as weak human resources, inadequate facilities, and minimal promotion. This study aims to identify ecotourism practices at Batu Lumbang, analyze stakeholder roles, and evaluate stakeholder collaboration to increase international tourist visits. Using a descriptive qualitative approach, data were collected through observation, interviews, documentation, and questionnaires, and analyzed with an interactive model. Findings reveal that Mangrove Ecotourism at Batu Lumbang meets criteria for attractive tourism: something to see, do, and buy. Stakeholder roles are categorized into primary, key, and secondary. The involvement of the pentahelix—government, local community, academia, media, and business—is crucial. Effective stakeholder collaboration is needed to enhance development and sustainable promotion of ecotourism.